Treatment of pregnancy-induced hypertension compared with labetalol, low dose aspirin and placebo - Xiang, Xuewen; Wang, Fang; Zhao, Ni; Zhou, Zhao (Cellular and Molecular Biology, 2020)
This study aimed to evaluate the maternal and fetal results in women undergoing antihypertensive therapy (low aspirin or labetalol) with mild to severe chronic hypertension relative to women without medicines. This randomized multi-center clinical trial was performed with random division into three groups of 393 pregnant women with mild to moderate chronic hypertension. From the beginning of the pregnancy to the end of the puerperium, the low dosage aspirin group (n = 129), the labetalol group (n = 127), and the drug-free or control group (n = 126) reported both mother and child results. Major variations in the presence of severely motherly hypertension, pre-eclampsia, renal failure, ECG shifts, and cardiovascular rupture between treatment groups (low doses of aspirin and labetalol) and control groups were noted. Repeated placenta and blood pressure control hospitalizations. (P<0.001) in the control group more often (untreated). The new babies were more vulnerable to gestational age (SGA), neonatal hypotension, neonatal Hyperbilirubinemia, and ICU (p <0.001 in contrast with the low-dose aspirin and control groups). In the control group, the proportion of premature babies was considerably higher than in the treatment group (p<0,05). A mild to moderate persistent high blood pressure during pregnancy therapy helps minimize mother and child occurrence. The use of labetalol is correlated with a higher incidence of SGA, neonatal hypotension, and neonatal hyperbilirubinemia relative to low-dose aspirin or control group.